HOUSEHOLD FOOD INSECURITY IS ASSOCIATED WITH BINGE EATING DISORDER AMONG ADOLESCENT IN SEMAMPIR DISTRICT, SURABAYA, INDONESIA - Dian Puteri Andani; Annis Catur Adi (Universitas Airlangga, 2021)
Teenage phase is a critical period of psychosocial development. Adolescent eating patterns are formed in this phase. Household food security is among factors which may infl uence eating pattern. Adolescent who are exposed to food insecure condition tend to experience stress, which one of the coping mechanisms is overeating and may develop binge eating disorder. The purpose of this study is to analyze association between household food security status and binge eating disorder in adolescent. This case control study involved 74 adolescents aged 16-18 years and their parents in Semampir District, Surabaya, Indonesia who were selected randomly using simple random sampling. Household food security was assessed by using the Household Food Insecurity Access Scale (HFIAS) and binge eating disorder is assessed by using Eating Disorder Diagnostic Scale (EDDS). The association between household food security and binge eating disorder was analyzed by Spearman’s correlation test. There was an association between food security status (p = 0,001) and binge eating disorder. Further analysis showed that adolescents at risk of food insecurity were 5,625 times more likely to experience a binge eating disorder. This study recommends to increase food security through economic empowerment of housewives and socialization about coping strategy for both parent and adolescent.